The Convergence Of Islamic Law And Positive Law In Marriage In Indonesia - Mulyanto (Gudang Jurnal Multidisiplin Ilmu, 2025)
Marriage Law in Indonesia is the result of the convergence between Islamic legal principles and state regulations, as outlined in Law Number 1 of 1974 on Marriage and the Compilation of Islamic Law (KHI). This study aims to analyze how Islamic law and positive law interact in regulating marriage and to what extent their convergence occurs in the practice of religious courts and within the Muslim community in Indonesia. The research employs a normative approach by analyzing sources of Islamic law, statutory regulations, and religious court rulings related to marriage. The findings indicate that although Indonesia’s marriage law is based on Sharia principles, several adjustments have been made to align with positive law to ensure justice and protection for all parties, particularly in aspects such as marriage registration, minimum marriage age, and women's rights. The convergence between Islamic law and positive law reflects efforts to harmonize religious values with national legal interests. However, challenges remain in its implementation, particularly concerning child marriage, polygamy, and divorce, which often spark debates in society. Therefore, further studies are needed to evaluate the effectiveness of Indonesia’s marriage regulations and how Islamic law can continue to adapt within the framework of a modern legal state.